Metode Dakwah Majelis Ta’lim Daarus Sholihin dalam Mengisahkan Sejarah Nabi Muhammad SAW Kepada Jama’ah Yasinan Kubro Melalui Pembacaan Kitab Maulid Al-Barzanji - Muhammad Firdaus; Wildan Yahya; Hendi Suhendi (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Majelis Ta’lim Daarus Sholihin is a place for seeking religious knowledge. In expanding its dakwah (Islamic preaching), the administrators of Majelis Ta’lim Daarus Sholihin have introduced an innovative approach to delivering religious knowledge through the Yasinan Kubro activity. The focus of the dakwah during Yasinan Kubro is narrating the history of Prophet Muhammad SAW to the congregation using the Maulid Al-Barzanji book. This study aims to identify the dakwah methods employed by the administrators of Majelis Ta’lim Daarus Sholihin. The research utilizes the dakwah theories of Dakwah Bil Lisan (preaching through speech), Dakwah Bil Hal (preaching through actions), and Dakwah Bil Qalam (preaching through writing). A qualitative method is used to examine how Dakwah Bil Lisan, Dakwah Bil Hal, and Dakwah Bil Qalam are implemented by the administrators during the Yasinan Kubro activity. The findings highlight that Dakwah Bil Lisan involves providing an understanding of Islam to the congregation through sermons. Dakwah Bil Hal involves demonstrating practical examples for the congregation to apply in their daily lives to develop virtuous characters. Dakwah Bil Qalam involves studying the Maulid Al-Barzanji book so that the congregation gains foundational knowledge of the history of Prophet Muhammad SAW. Thus, Majelis Ta’lim Daarus Sholihin provides facilities to the congregation by offering comprehensive Islamic knowledge. Abstrak. Majelis Ta’lim Daarus Sholihin merupakan sebuah tempat untuk menuntut ilmu agama. Dalam melebarkan dakwahnya, Pengurus Majelis Ta’lim Daarus Sholihin membuat inovasi dalam memberikan ilmu agama, yaitu kegiatan Yasinan Kubro. Fokus dakwah yang dilakukan pengurus Majelis Ta’lim Daarus Sholihin pada kegiatan Yasinan Kubro ialah mengisahkan sejarah Nabi Muhammad SAW kepada jama’ah dengan kajian Kitab Maulid Al-Barzanji. Penelitian ini dilakukan untuk mengetahui metode dakwah pengurus Majelis Ta’lim Daarus Sholihin. Penelitian ini menggunakan teori dakwah, yaitu Dakwah Bil Lisan, Dakwah Bil Hal, Dakwah Bil Qalam. Metode kualitatif digunakan untuk mengkaji bagaimana Dakwah Bil Lisan, Dakwah Bil Hal, Dakwah Bil Qalam yang dilakukan pengurus Majelis Ta’lim Daarus Sholihin pada kegiatan Yasinan Kubro. Temuan penelitian menyoroti Dakwah Bil Lisan: memberikan pemahaman agama islam kepada jama’ah melalui ceramah. Dakwah Bil Hal: memberikan contoh kepada jama’ah untuk diaplikasikan sehari-hari dan membentuk pribadi berakhlakul karimah. Dakwah Bil Qalam: memberikan kajian Kitab Maulid Al-Barzanji agar jama’ah mengetahui sejarah dasar Nabi Muhammad SAW. Dengan demikian, Mjelis Ta’lim Daarus Sholihin memberikan fasilitas kepada jama’ah dari segi memberikan pemahaman agama islam.